Hydrologic History Regulates Microbial Biofilm Diversity and Ecosystem Function - Allison R. Rober; Leah C. Reese; Shawn P. Brown; Katherine D. McMahon; Stilianos Louca; Jillian Cieslik; Evan S. Kane; Merritt R. Turetsky; Kevin H. Wyatt (Environmental Microbiology, 2026)
Aquatic biofilms are an understudied component of northern peatlands and are expected to play a more prominent role in ecosystem processes in areas where aquatic habitat is expanding. The goal of this study was to investigate how hydrologic history influences biofilm diversity and functional genes. This study was conducted in a long‐term water table manipulation that simulates drought (lowered water table treatment) and flooding (raised water table treatment) conditions relative to a control treatment (no manipulation). We used a combination of metabarcoding and metagenomic approaches to (1) examine the diversity of eukaryotic algae, cyanobacteria, bacteria and fungi within the biofilm and (2) identify functional genes associated with alternating wet‐dry transitional states. Historical flooding, but not drought, led to broad changes in composition and functional genes, especially those associated with carbon metabolism and nitrogen cycling. Differences were related to changes in relative abundance rather than the presence/absence of individual taxa or genes. Hydrologic history influenced community diversity by reducing interspecific competition or by alleviating resource limitation. These findings show that hydrologic history regulates species membership of the community (and thereby associated genes) but differences in water chemistry and interspecific interactions alter the relative abundance of species and their functional potential.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Legacy Effects of Plant Community Structure Are Manifested in Microbial Biofilm Development With Consequences for Ecosystem CO 2 Emissions - Kevin H. Wyatt; Jillian Cieslik; Catherine M. Dieleman; Evan S. Kane; Allison R. Rober; Barrett Sullivan; Merritt R. Turetsky (Global Change Biology, 2024)
To better understand linkages between hydrology and ecosystem carbon flux in northern aquatic ecosystems, we evaluated the relationship between plant communities, biofilm development, and carbon dioxide (CO 2 ) exchange following long‐term changes in hydrology in an Alaskan fen. We quantified seasonal variation in biofilm composition and CO 2 exchange in response to lowered and raised water table position (relative to a control) during years with varying levels of background dissolved organic carbon (DOC). We then used nutrient‐diffusing substrates (NDS) to evaluate cause–effect relationships between changes in plant subsidies (i.e., leachates) and biofilm composition among water table treatments. We found that background DOC concentration determined whether plant subsidies promoted net autotrophy or heterotrophy on NDS. In conditions where background DOC was ≤ 40 mg L −1 , plant subsidies promoted an autotrophic biofilm. Conversely, when background DOC concentration was ≥ 50 mg L −1 , plant subsidies promoted heterotrophy. Greater light attenuation associated with elevated levels of DOC may have overwhelmed the stimulatory effect of nutrients on autotrophic microbes by constraining photosynthesis while simultaneously allowing heterotrophs to outcompete autotrophs for available nutrients. At the ecosystem level, conditions that favored an autotrophic biofilm resulted in net CO 2 uptake among all water table treatments, whereas the site was a net source of CO 2 to the atmosphere in conditions that supported greater heterotrophy. Taken together, these findings show that hydrologic history interacts with changes in dominant plant functional groups to alter biofilm composition, which has consequences for ecosystem CO 2 exchange.

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Post-fire Recovery of Soil Organic Layer Carbon in Canadian Boreal Forests - Kristen E. Bill; Catherine M. Dieleman; Jennifer L. Baltzer; Geneviève É. Degré-Timmons; Michelle C. Mack; Nicola J. Day; Steve G. Cumming; Xanthe J. Walker; Merritt R. Turetsky (Ecosystems, 2023)

Permafrost thaw causes large carbon loss in boreal peatlands while changes to peat quality are limited - Lorna I. Harris; David Olefeldt; Nicolas Pelletier; Christian Blodau; Klaus‐Holger Knorr; Julie Talbot; Liam Heffernan; Merritt Turetsky (Global Change Biology, 2023)
Rapid, ongoing permafrost thaw of peatlands in the discontinuous permafrost zone is exposing a globally significant store of soil carbon (C) to microbial processes. Mineralization and release of this peat C to the atmosphere as greenhouse gases is a potentially important feedback to climate change. Here we investigated the effects of permafrost thaw on peat C at a peatland complex in western Canada. We collected 15 complete peat cores (between 2.7 and 4.5 m deep) along four chronosequences, from elevated permafrost peat plateaus to saturated thermokarst bogs that thawed up to 600 years ago. The peat cores were analysed for peat C storage and peat quality, as indicated by decomposition proxies (FTIR and C/N ratios) and potential decomposability using a 200‐day aerobic laboratory incubation. Our results suggest net C loss following thaw, with average total peat C stocks decreasing by ~19.3 ± 7.2 kg C m −2 over −2 . We estimate ~19% (±5.8%) of deep peat (>40 cm below surface) C is lost following thaw (average 26 ± 7.9 kg C m −2 over

Permafrost thaw induces short‐term increase in vegetation productivity in northwestern Canada - Emily L. Ogden; Steven G. Cumming; Sharon L. Smith; Merritt R. Turetsky; Jennifer L. Baltzer (Global Change Biology, 2023)
Over the past several decades, various trends in vegetation productivity, from increases to decreases, have been observed throughout Arctic–Boreal ecosystems. While some of this variation can be explained by recent climate warming and increased disturbance, very little is known about the impacts of permafrost thaw on productivity across diverse vegetation communities. Active layer thickness data from 135 permafrost monitoring sites along a 10° latitudinal transect of the Northwest Territories, Canada, paired with a Landsat time series of normalized difference vegetation index from 1984 to 2019, were used to quantify the impacts of changing permafrost conditions on vegetation productivity. We found that active layer thickness contributed to the observed variation in vegetation productivity in recent decades in the northwestern Arctic–Boreal, with the highest rates of greening occurring at sites where the near‐surface permafrost recently had thawed. However, the greening associated with permafrost thaw was not sustained after prolonged periods of thaw and appeared to diminish after the thaw front extended outside the plants' rooting zone. Highest rates of greening were found at the mid‐transect sites, between 62.4° N and 65.2° N, suggesting that more southernly sites may have already surpassed the period of beneficial permafrost thaw, while more northern sites may have yet to reach a level of thaw that supports enhanced vegetation productivity. These results indicate that the response of vegetation productivity to permafrost thaw is highly dependent on the extent of active layer thickening and that increases in productivity may not continue in the coming decades.

Structuring Life After Death: Plant Leachates Promote CO2 Uptake by Regulating Microbial Biofilm Interactions in a Northern Peatland Ecosystem - Allison R. Rober; Allyson J. Lankford; Evan S. Kane; Merritt R. Turetsky; Kevin H. Wyatt (Ecosystems, 2023)
Shifts in plant functional groups associated with climate change have the potential to influence peatland carbon storage by altering the amount and composition of organic matter available to aquatic microbial biofilms. The goal of this study was to evaluate the potential for plant subsidies to regulate ecosystem carbon flux (CO 2 ) by governing the relative proportion of primary producers (microalgae) and heterotrophic decomposers (heterotrophic bacteria) during aquatic biofilm development in an Alaskan fen. We evaluated biofilm composition and CO 2 flux inside mesocosms with and without nutrients (both nitrogen and phosphorus), organic carbon (glucose), and leachates from common peatland plants (moss, sedge, shrub, horsetail). Experimental mesocosms were exposed to either natural sunlight or placed under a dark canopy to evaluate the response of decomposers to nutrients and carbon subsidies with and without algae, respectively. Algae were limited by inorganic nutrients and heterotrophic bacteria were limited by organic carbon. The quality of organic matter varied widely among plants and leachate nutrient content, more so than carbon quality, influenced biofilm composition. By alleviating nutrient limitation of algae, plant leachates shifted the biofilm community toward autotrophy in the light-transparent treatments, resulting in a significant reduction in CO 2 emissions compared to the control. Without the counterbalance from algal photosynthesis, a heterotrophic biofilm significantly enhanced CO 2 emissions in the presence of plant leachates in the dark. These results show that plants not only promote carbon uptake directly through photosynthesis, but also indirectly through a surrogate, the phototrophic microbes.

Material Legacies and Environmental Constraints Underlie Fire Resilience of a Dominant Boreal Forest Type - Nicola J. Day; Jill F. Johnstone; Kirsten A. Reid; Steven G. Cumming; Michelle C. Mack; Merritt R. Turetsky; Xanthe J. Walker; Jennifer L. Baltzer (Ecosystems, 2023)
Resilience of plant communities to disturbance is supported by multiple mechanisms, including ecological legacies affecting propagule availability, species’ environmental tolerances, and biotic interactions. Understanding the relative importance of these mechanisms for plant community resilience supports predictions of where and how resilience will be altered with disturbance. We tested mechanisms underlying resilience of forests dominated by black spruce ( Picea mariana ) to fire disturbance across a heterogeneous forest landscape in the Northwest Territories, Canada. We combined surveys of naturally regenerating seedlings at 219 burned plots with experimental manipulations of ecological legacies via seed addition of four tree species and vertebrate exclosures to limit granivory and herbivory at 30 plots varying in moisture and fire severity. Black spruce recovery was greatest where it dominated pre-fire, at wet sites with deep residual soil organic layers, and fire conditions of low soil or canopy combustion and longer return intervals. Experimental addition of seed indicated all species were seed-limited, emphasizing the importance of propagule legacies. Black spruce and birch ( Betula papyrifera ) recruitment were enhanced with vertebrate exclusion. Our combination of observational and experimental studies demonstrates black spruce is vulnerable to effects of increased fire activity that erode ecological legacies. Moreover, black spruce relies on wet areas with deep soil organic layers where other species are less competitive. However, other species can colonize these areas if enough seed is available or soil moisture is altered by climate change. Testing mechanisms underlying species’ resilience to disturbance aids predictions of where vegetation will transform with effects of climate change.

Lowering water table reduces carbon sink strength and carbon stocks in northern peatlands - Min Jung Kwon; Ashley Ballantyne; Philippe Ciais; Chunjing Qiu; Elodie Salmon; Nina Raoult; Bertrand Guenet; Mathias Göckede; Eugénie S. Euskirchen; Hannu Nykänen; Edward A. G. Schuur; Merritt R. Turetsky; et al. (Global Change Biology, 2022)
Peatlands at high latitudes have accumulated >400 Pg carbon (C) because saturated soil and cold temperatures suppress C decomposition. This substantial amount of C in Arctic and Boreal peatlands is potentially subject to increased decomposition if the water table (WT) decreases due to climate change, including permafrost thaw‐related drying. Here, we optimize a version of the Organizing Carbon and Hydrology In Dynamic Ecosystems model (ORCHIDEE‐PCH4) using site‐specific observations to investigate changes in CO 2 and CH 4 fluxes as well as C stock responses to an experimentally manipulated decrease of WT at six northern peatlands. The unmanipulated control peatlands, with the WT −2 year −1 ; including 6 ± 7 g C–CH 4 m −2 year −1 emission). We found, however, that lowering the WT by 10 cm reduced the CO 2 sink by 13 ± 15 g C m −2 year −1 and decreased CH 4 emission by 4 ± 4 g CH 4 m −2 year −1 , thus accumulating less C over 100 years (0.2 ± 0.2 kg C m −2 ). Yet, the reduced emission of CH 4 , which has a larger greenhouse warming potential, resulted in a net decrease in greenhouse gas balance by 310 ± 360 g CO 2‐eq m −2 year −1 . Peatlands with the initial WT close to the soil surface were more vulnerable to C loss: Non‐permafrost peatlands lost >2 kg C m −2 over 100 years when WT is lowered by 50 cm, while permafrost peatlands temporally switched from C sinks to sources. These results highlight that reductions in C storage capacity in response to drying of northern peatlands are offset in part by reduced CH 4 emissions, thus slightly reducing the positive carbon climate feedbacks of peatlands under a warmer and drier future climate scenario.

Deep roots of Carex aquatilis have greater ammonium uptake capacity than shallow roots in peatlands following permafrost thaw - Lucas J. Albano; Merritt R. Turetsky; Michelle C. Mack; Evan S. Kane (Plant and Soil, 2021)

Letter: Trophic interactions regulate peatland carbon cycling - Kevin H. Wyatt; Kevin S. McCann; Allison R. Rober; Merritt R. Turetsky (Ecology Letters, 2021)
Peatlands are the most efficient natural ecosystems for long‐term storage of atmospheric carbon. Our understanding of peatland carbon cycling is based entirely on bottom‐up controls regulated by low nutrient availability. Recent studies have shown that top‐down controls through predator‐prey dynamics can influence ecosystem function, yet this has not been evaluated in peatlands to date. Here, we used a combination of nutrient enrichment and trophic‐level manipulation to test the hypothesis that interactions between nutrient availability (bottom‐up) and predation (top‐down) influence peatland carbon fluxes. Elevated nutrients stimulated bacterial biomass and organic matter decomposition. In the absence of top‐down regulation, carbon dioxide (CO 2 ) respiration driven by greater decomposition was offset by elevated algal productivity. Herbivores accelerated CO 2 emissions by removing algal biomass, while predators indirectly reduced CO 2 emissions by muting herbivory in a trophic cascade. This study demonstrates that trophic interactions can mitigate CO 2 emissions associated with elevated nutrient levels in northern peatlands.

Wildfire combustion and carbon stocks in the southern Canadian boreal forest: Implications for a warming world - Catherine M. Dieleman; Brendan M. Rogers; Stefano Potter; Sander Veraverbeke; Jill F. Johnstone; Jocelyne Laflamme; Kylen Solvik; Xanthe J. Walker; Michelle C. Mack; Merritt R. Turetsky (Global Change Biology, 2020)
Boreal wildfires are increasing in intensity, extent, and frequency, potentially intensifying carbon emissions and transitioning the region from a globally significant carbon sink to a source. The productive southern boreal forests of central Canada already experience relatively high frequencies of fire, and as such may serve as an analog of future carbon dynamics for more northern forests. Fire–carbon dynamics in southern boreal systems are relatively understudied, with limited investigation into the drivers of pre‐fire carbon stocks or subsequent combustion. As part of NASA's Arctic‐Boreal Vulnerability Experiment, we sampled 79 stands (47 burned, 32 unburned) throughout central Saskatchewan to characterize above‐ and belowground carbon stocks and combustion rates in relation to historical land use, vegetation characteristics, and geophysical attributes. We found southern boreal forests emitted an average of 3.3 ± 1.1 kg C/m 2 from field sites. The emissions from southern boreal stands varied as a function of stand age, fire weather conditions, ecozone, and soil moisture class. Sites affected by historical timber harvesting had greater combustion rates due to faster carbon stock recovery rates than sites recovering from wildfire events, indicating that different boreal forest land use practices can generate divergent carbon legacy effects. We estimate the 2015 fire season in Saskatchewan emitted a total of 36.3 ± 15.0 Tg C, emphasizing the importance of southern boreal fires for regional carbon budgets. Using the southern boreal as an analog, the northern boreal may undergo fundamental shifts in forest structure and carbon dynamics, becoming dominated by stands 2 less than current mature northern boreal stands. Our latitudinal approach reinforces previous studies showing that northern boreal stands are at a high risk of holding less carbon under changing disturbance conditions.

Tradeoffs between phenotypic plasticity and local adaptation influence the ecophysiology of the moss, Sphagnum magellanicum - Tobi A. Oke; Merritt R. Turetsky; David J. Weston; Jonathan A. Shaw (Oecologia, 2020)

Climate change decreases the cooling effect from postfire albedo in boreal North America - Stefano Potter; Kylen Solvik; Angela Erb; Scott J. Goetz; Jill F. Johnstone; Michelle C. Mack; James T. Randerson; Miguel O. Román; Crystal L. Schaaf; Merritt R. Turetsky; Sander Veraverbeke; Xanthe J. Walker; et al. (Global Change Biology, 2020)
Fire is a primary disturbance in boreal forests and generates both positive and negative climate forcings. The influence of fire on surface albedo is a predominantly negative forcing in boreal forests, and one of the strongest overall, due to increased snow exposure in the winter and spring months. Albedo forcings are spatially and temporally heterogeneous and depend on a variety of factors related to soils, topography, climate, land cover/vegetation type, successional dynamics, time since fire, season, and fire severity. However, how these variables interact to influence albedo is not well understood, and quantifying these relationships and predicting postfire albedo becomes increasingly important as the climate changes and management frameworks evolve to consider climate impacts. Here we developed a MODIS‐derived ‘blue sky’ albedo product and a novel machine learning modeling framework to predict fire‐driven changes in albedo under historical and future climate scenarios across boreal North America. Converted to radiative forcing (RF), we estimated that fires generate an annual mean cooling of −1.77 ± 1.35 W/m 2 from albedo under historical climate conditions (1971–2000) integrated over 70 years postfire. Increasing postfire albedo along a south–north climatic gradient was offset by a nearly opposite gradient in solar insolation, such that large‐scale spatial patterns in RF were minimal. Our models suggest that climate change will lead to decreases in mean annual postfire albedo, and hence a decreasing strength of the negative RF, a trend dominated by decreased snow cover in spring months. Considering the range of future climate scenarios and model uncertainties, we estimate that for fires burning in the current era (2016) the cooling effect from long‐term postfire albedo will be reduced by 15%–28% due to climate change.

Wildfire severity reduces richness and alters composition of soil fungal communities in boreal forests of western Canada - Nicola J. Day; Kari E. Dunfield; Jill F. Johnstone; Michelle C. Mack; Merritt R. Turetsky; Xanthe J. Walker; Alison L. White; Jennifer L. Baltzer (Global Change Biology, 2019)
Wildfire is the dominant disturbance in boreal forests and fire activity is increasing in these regions. Soil fungal communities are important for plant growth and nutrient cycling postfire but there is little understanding of how fires impact fungal communities across landscapes, fire severity gradients, and stand types in boreal forests. Understanding relationships between fungal community composition, particularly mycorrhizas, and understory plant composition is therefore important in predicting how future fire regimes may affect vegetation. We used an extreme wildfire event in boreal forests of Canada's Northwest Territories to test drivers of fungal communities and assess relationships with plant communities. We sampled soils from 39 plots 1 year after fire and 8 unburned plots. High‐throughput sequencing (MiSeq, ITS) revealed 2,034 fungal operational taxonomic units. We found soil pH and fire severity (proportion soil organic layer combusted), and interactions between these drivers were important for fungal community structure (composition, richness, diversity, functional groups). Where fire severity was low, samples with low pH had higher total fungal, mycorrhizal, and saprotroph richness compared to where severity was high. Increased fire severity caused declines in richness of total fungi, mycorrhizas, and saprotrophs, and declines in diversity of total fungi and mycorrhizas. The importance of stand age (a surrogate for fire return interval) for fungal composition suggests we could detect long‐term successional patterns even after fire. Mycorrhizal and plant community composition, richness, and diversity were weakly but significantly correlated. These weak relationships and the distribution of fungi across plots suggest that the underlying driver of fungal community structure is pH, which is modified by fire severity. This study shows the importance of edaphic factors in determining fungal community structure at large scales, but suggests these patterns are mediated by interactions between fire and forest stand composition.

The response of boreal peatland community composition and NDVI to hydrologic change, warming, and elevated carbon dioxide - Mara Y. McPartland; Evan S. Kane; Michael J. Falkowski; Randy Kolka; Merritt R. Turetsky; Brian Palik; Rebecca A. Montgomery (Global Change Biology, 2019)
Widespread changes in arctic and boreal Normalized Difference Vegetation Index ( NDVI ) values captured by satellite platforms indicate that northern ecosystems are experiencing rapid ecological change in response to climate warming. Increasing temperatures and altered hydrology are driving shifts in ecosystem biophysical properties that, observed by satellites, manifest as long‐term changes in regional NDVI . In an effort to examine the underlying ecological drivers of these changes, we used field‐scale remote sensing of NDVI to track peatland vegetation in experiments that manipulated hydrology, temperature, and carbon dioxide ( CO 2 ) levels. In addition to NDVI , we measured percent cover by species and leaf area index ( LAI ). We monitored two peatland types broadly representative of the boreal region. One site was a rich fen located near Fairbanks, Alaska, at the Alaska Peatland Experiment ( APEX ), and the second site was a nutrient‐poor bog located in Northern Minnesota within the Spruce and Peatland Responses Under Changing Environments ( SPRUCE ) experiment. We found that NDVI decreased with long‐term reductions in soil moisture at the APEX site, coincident with a decrease in photosynthetic leaf area and the relative abundance of sedges. We observed increasing NDVI with elevated temperature at the SPRUCE site, associated with an increase in the relative abundance of shrubs and a decrease in forb cover. Warming treatments at the SPRUCE site also led to increases in the LAI of the shrub layer. We found no strong effects of elevated CO 2 on community composition. Our findings support recent studies suggesting that changes in NDVI observed from satellite platforms may be the result of changes in community composition and ecosystem structure in response to climate warming.

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

A decade of boreal rich fen greenhouse gas fluxes in response to natural and experimental water table variability - David Olefeldt; Eugénie S. Euskirchen; Jennifer Harden; Evan Kane; A. David McGuire; Mark P. Waldrop; Merritt R. Turetsky (Global Change Biology, 2017)
Rich fens are common boreal ecosystems with distinct hydrology, biogeochemistry and ecology that influence their carbon (C) balance. We present growing season soil chamber methane emission ( F CH 4 ), ecosystem respiration ( ER ), net ecosystem exchange ( NEE ) and gross primary production ( GPP ) fluxes from a 9‐years water table manipulation experiment in an Alaskan rich fen. The study included major flood and drought years, where wetting and drying treatments further modified the severity of droughts. Results support previous findings from peatlands that drought causes reduced magnitude of growing season F CH 4 , GPP and NEE , thus reducing or reversing their C sink function. Experimentally exacerbated droughts further reduced the capacity for the fen to act as a C sink by causing shifts in vegetation and thus reducing magnitude of maximum growing season GPP in subsequent flood years by ~15% compared to control plots. Conversely, water table position had only a weak influence on ER , but dominant contribution to ER switched from autotrophic respiration in wet years to heterotrophic in dry years. Droughts did not cause inter‐annual lag effects on ER in this rich fen, as has been observed in several nutrient‐poor peatlands. While ER was dependent on soil temperatures at 2 cm depth, F CH 4 was linked to soil temperatures at 25 cm. Inter‐annual variability of deep soil temperatures was in turn dependent on wetness rather than air temperature, and higher F CH 4 in flooded years was thus equally due to increased methane production at depth and decreased methane oxidation near the surface. Short‐term fluctuations in wetness caused significant lag effects on F CH 4 , but droughts caused no inter‐annual lag effects on F CH 4 . Our results show that frequency and severity of droughts and floods can have characteristic effects on the exchange of greenhouse gases, and emphasize the need to project future hydrological regimes in rich fens.

Losing Legacies, Ecological Release, and Transient Responses: Key Challenges for the Future of Northern Ecosystem Science - Merritt R. Turetsky; Jennifer L. Baltzer; Jill F. Johnstone; Michelle C. Mack; Kevin McCann; Edward A. G. Schuur (Ecosystems, 2017)

A Thermodynamic Analysis of Soil Ecosystem Development in Northern Wetlands - Eric J. Chapman; Daniel L. Childers; Everett L. Shock; Merritt R. Turetsky (Wetlands, 2016)

The effect of long-term drying associated with experimental drainage and road construction on vegetation composition and productivity in boreal fens - Courtney A. Miller; Brian W. Benscoter; Merritt R. Turetsky (Wetlands Ecology and Management, 2015)

A pan‐Arctic synthesis of CH 4 and CO 2 production from anoxic soil incubations - Claire C. Treat; Susan M. Natali; Jessica Ernakovich; Colleen M. Iversen; Massimo Lupascu; Anthony David McGuire; Richard J. Norby; Taniya Roy Chowdhury; Andreas Richter; Hana Šantrůčková; Christina Schädel; Edward A. G. Schuur; et al. (Global Change Biology, 2015)
Permafrost thaw can alter the soil environment through changes in soil moisture, frequently resulting in soil saturation, a shift to anaerobic decomposition, and changes in the plant community. These changes, along with thawing of previously frozen organic material, can alter the form and magnitude of greenhouse gas production from permafrost ecosystems. We synthesized existing methane (CH 4 ) and carbon dioxide (CO 2 ) production measurements from anaerobic incubations of boreal and tundra soils from the geographic permafrost region to evaluate large‐scale controls of anaerobic CO 2 and CH 4 production and compare the relative importance of landscape‐level factors (e.g., vegetation type and landscape position), soil properties (e.g., pH, depth, and soil type), and soil environmental conditions (e.g., temperature and relative water table position). We found fivefold higher maximum CH 4 production per gram soil carbon from organic soils than mineral soils. Maximum CH 4 production from soils in the active layer (ground that thaws and refreezes annually) was nearly four times that of permafrost per gram soil carbon, and CH 4 production per gram soil carbon was two times greater from sites without permafrost than sites with permafrost. Maximum CH 4 and median anaerobic CO 2 production decreased with depth, while CO 2 :CH 4 production increased with depth. Maximum CH 4 production was highest in soils with herbaceous vegetation and soils that were either consistently or periodically inundated. This synthesis identifies the need to consider biome, landscape position, and vascular/moss vegetation types when modeling CH 4 production in permafrost ecosystems and suggests the need for longer‐term anaerobic incubations to fully capture CH 4 dynamics. Our results demonstrate that as climate warms in arctic and boreal regions, rates of anaerobic CO 2 and CH 4 production will increase, not only as a result of increased temperature, but also from shifts in vegetation and increased ground saturation that will accompany permafrost thaw.

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

Circumpolar assessment of permafrost C quality and its vulnerability over time using long‐term incubation data - Christina Schädel; Edward A. G. Schuur; Rosvel Bracho; Bo Elberling; Christian Knoblauch; Hanna Lee; Yiqi Luo; Gaius R. Shaver; Merritt R. Turetsky (Global Change Biology, 2014)
High‐latitude ecosystems store approximately 1700 Pg of soil carbon (C), which is twice as much C as is currently contained in the atmosphere. Permafrost thaw and subsequent microbial decomposition of permafrost organic matter could add large amounts of C to the atmosphere, thereby influencing the global C cycle. The rates at which C is being released from the permafrost zone at different soil depths and across different physiographic regions are poorly understood but crucial in understanding future changes in permafrost C storage with climate change. We assessed the inherent decomposability of C from the permafrost zone by assembling a database of long‐term (>1 year) aerobic soil incubations from 121 individual samples from 23 high‐latitude ecosystems located across the northern circumpolar permafrost zone. Using a three‐pool (i.e., fast, slow and passive) decomposition model, we estimated pool sizes for C fractions with different turnover times and their inherent decomposition rates using a reference temperature of 5 °C. Fast cycling C accounted for less than 5% of all C in both organic and mineral soils whereas the pool size of slow cycling C increased with C : N. Turnover time at 5 °C of fast cycling C typically was below 1 year, between 5 and 15 years for slow turning over C, and more than 500 years for passive C. We project that between 20 and 90% of the organic C could potentially be mineralized to CO 2 within 50 incubation years at a constant temperature of 5 °C, with vulnerability to loss increasing in soils with higher C : N. These results demonstrate the variation in the vulnerability of C stored in permafrost soils based on inherent differences in organic matter decomposability, and point toward C : N as an index of decomposability that has the potential to be used to scale permafrost C loss across landscapes.

Altered Composition and Microbial versus UV-Mediated Degradation of Dissolved Organic Matter in Boreal Soils Following Wildfire - David Olefeldt; Merritt R. Turetsky; Christian Blodau (Ecosystems, 2013)

The response of soil organic carbon of a rich fen peatland in interior Alaska to projected climate change - Zhaosheng Fan; Anthony David McGuire; Merritt R. Turetsky; Jennifer W. Harden; James Michael Waddington; Evan S. Kane (Global Change Biology, 2013)
It is important to understand the fate of carbon in boreal peatland soils in response to climate change because a substantial change in release of this carbon as CO 2 and CH 4 could influence the climate system. The goal of this research was to synthesize the results of a field water table manipulation experiment conducted in a boreal rich fen into a process‐based model to understand how soil organic carbon ( SOC ) of the rich fen might respond to projected climate change. This model, the peatland version of the dynamic organic soil Terrestrial Ecosystem Model (peatland DOS ‐ TEM ), was calibrated with data collected during 2005–2011 from the control treatment of a boreal rich fen in the Alaska Peatland Experiment ( APEX ). The performance of the model was validated with the experimental data measured from the raised and lowered water‐table treatments of APEX during the same period. The model was then applied to simulate future SOC dynamics of the rich fen control site under various CO 2 emission scenarios. The results across these emissions scenarios suggest that the rate of SOC sequestration in the rich fen will increase between year 2012 and 2061 because the effects of warming increase heterotrophic respiration less than they increase carbon inputs via production. However, after 2061, the rate of SOC sequestration will be weakened and, as a result, the rich fen will likely become a carbon source to the atmosphere between 2062 and 2099. During this period, the effects of projected warming increase respiration so that it is greater than carbon inputs via production. Although changes in precipitation alone had relatively little effect on the dynamics of SOC , changes in precipitation did interact with warming to influence SOC dynamics for some climate scenarios.

Environmental and physical controls on northern terrestrial methane emissions across permafrost zones - David Olefeldt; Merritt R. Turetsky; Patrick M. Crill; A. David McGuire (Global Change Biology, 2013)
Methane ( CH 4 ) emissions from the northern high‐latitude region represent potentially significant biogeochemical feedbacks to the climate system. We compiled a database of growing‐season CH 4 emissions from terrestrial ecosystems located across permafrost zones, including 303 sites described in 65 studies. Data on environmental and physical variables, including permafrost conditions, were used to assess controls on CH 4 emissions. Water table position, soil temperature, and vegetation composition strongly influenced emissions and had interacting effects. Sites with a dense sedge cover had higher emissions than other sites at comparable water table positions, and this was an effect that was more pronounced at low soil temperatures. Sensitivity analysis suggested that CH 4 emissions from ecosystems where the water table on average is at or above the soil surface (wet tundra, fen underlain by permafrost, and littoral ecosystems) are more sensitive to variability in soil temperature than drier ecosystems (palsa dry tundra, bog, and fen), whereas the latter ecosystems conversely are relatively more sensitive to changes of the water table position. Sites with near‐surface permafrost had lower CH 4 fluxes than sites without permafrost at comparable water table positions, a difference that was explained by lower soil temperatures. Neither the active layer depth nor the organic soil layer depth was related to CH 4 emissions. Permafrost thaw in lowland regions is often associated with increased soil moisture, higher soil temperatures, and increased sedge cover. In our database, lowland thermokarst sites generally had higher emissions than adjacent sites with intact permafrost, but emissions from thermokarst sites were not statistically higher than emissions from permafrost‐free sites with comparable environmental conditions. Overall, these results suggest that future changes to terrestrial high‐latitude CH 4 emissions will be more proximately related to changes in moisture, soil temperature, and vegetation composition than to increased availability of organic matter following permafrost thaw.

Contributions of algae to GPP and DOC production in an Alaskan fen: effects of historical water table manipulations on ecosystem responses to a natural flood - Kevin H. Wyatt; Merritt R. Turetsky; Allison R. Rober; Danilo Giroldo; Evan S. Kane; R. Jan Stevenson (Oecologia, 2012)

Abundance of microbial genes associated with nitrogen cycling as indices of biogeochemical process rates across a vegetation gradient in Alaska - Dorthe Groth Petersen; Steven J. Blazewicz; Mary Firestone; Donald J. Herman; Merritt Turetsky; Mark Waldrop (Environmental Microbiology, 2012)
Summary Nitrification and denitrification processes are crucial to plant nutrient availability, eutrophication and greenhouse gas production both locally and globally. Unravelling the major environmental predictors for nitrification and denitrification is thus pivotal in order to understand and model environmental nitrogen (N) cycling. Here, we sampled five plant community types characteristic of interior Alaska, including black spruce, bog birch, tussock grass and two fens. We assessed abundance of functional genes affiliated with nitrification (bacterial and archaeal amoA ) and denitrification ( nirK / S and nosZ ) using qPCR, soil characteristics, potential nitrification and denitrification rates (PNR and PDR) and gross mineralization rates. The main chemical and biological predictors for PNR and PDR were assigned through path analysis. The potential N cycling rates varied dramatically between sites, from some of the highest (in fens) to some of the lowest (in black spruce) measured globally. Based on path analysis, functional gene abundances were the most important variables to predict potential rates. PNR was best explained by bacterial amoA gene abundance followed by ammonium content, whereas PDR was best explained directly by nosZ gene abundance and indirectly by nirK /S gene abundance and nitrate. Hence, functional gene abundance is a valuable index that integrates recent environmental history and recent process activity, and therefore is a good predictor of potential rates. The results of this study contribute to our understanding of the relative importance of different biological and chemical factors in driving the potential for nitrification and denitrification across terrestrial ecosystems.

Impacts of climate change on fire activity and fire management in the circumboreal forest - MIKE FLANNIGAN; BRIAN STOCKS; MERRITT TURETSKY; MIKE WOTTON (Global Change Biology, 2009)
Forest fires are a significant and natural element of the circumboreal forest. Fire activity is strongly linked to weather, and increased fire activity due to climate change is anticipated or arguably has already occurred. Recent studies suggest a doubling of area burned along with a 50% increase in fire occurrence in parts of the circumboreal by the end of this century. Fire management agencies' ability to cope with these increases in fire activity is limited, as these organizations operate with a narrow margin between success and failure; a disproportionate number of fires may escape initial attack under a warmer climate, resulting in an increase in area burned that will be much greater than the corresponding increase in fire weather severity. There may be only a decade or two before increased fire activity means fire management agencies cannot maintain their current levels of effectiveness.

Interactive Effects of Fire, Soil Climate, and Moss on CO2 Fluxes in Black Spruce Ecosystems of Interior Alaska - Jonathan A. O’Donnell; Merritt R. Turetsky; Jennifer W. Harden; Kristen L. Manies; Lee E. Pruett; Gordon Shetler; Jason C. Neff (Ecosystems, 2009)

Effects of wildfire and permafrost on soil organic matter and soil climate in interior Alaska - JENNIFER W. HARDEN; KRISTEN L. MANIES; MERRITT R. TURETSKY; JASON C. NEFF (Global Change Biology, 2006)
The influence of discontinuous permafrost on ground‐fuel storage, combustion losses, and postfire soil climates was examined after a wildfire near Delta Junction, AK in July 1999. At this site, we sampled soils from a four‐way site comparison of burning (burned and unburned) and permafrost (permafrost and nonpermafrost). Soil organic layers (which comprise ground‐fuel storage) were thicker in permafrost than nonpermafrost soils both in burned and unburned sites. While we expected fire severity to be greater in the drier site (without permafrost), combustion losses were not significantly different between the two burned sites. Overall, permafrost and burning had significant effects on physical soil variables. Most notably, unburned permafrost sites with the thickest organic mats consistently had the coldest temperatures and wettest mineral soil, while soils in the burned nonpermafrost sites were warmer and drier than the other soils. For every centimeter of organic mat thickness, temperature at 5 cm depth was about 0.5°C cooler during summer months. We propose that organic soil layers determine to a large extent the physical and thermal setting for variations in vegetation, decomposition, and carbon balance across these landscapes. In particular, the deep organic layers maintain the legacies of thermal and nutrient cycling governed by fire and revegetation. We further propose that the thermal influence of deep organic soil layers may be an underlying mechanism responsible for large regional patterns of burning and regrowth, detected in fractal analyses of burn frequency and area. Thus, fractal geometry can potentially be used to analyze changes in state of these fire prone systems.

Decomposition and Organic Matter Quality in Continental Peatlands: The Ghost of Permafrost Past - Merritt R. Turetsky (Ecosystems, 2004)

Dating recent peat deposits - Merritt R. Turetsky; Sturt W. Manning; R. Kelman Wieder (Wetlands, 2004)